(untitled) (Research, Society and Development, 2020)
Since the colonization of Brazil, the Atlantic Forest management, especially of the restinga vegetation located in coastal zones, represents a challenge to be faced by the coastal community. The data is alarming and ratify the loss of forest areas in these five centuries of history, concurrent to the increase of urbanization in coastal regions, proving the difficulty in conciliating human occupation and preservation of forests. This work aims to fill a legal hiatus recurrent in urban areas or urban expansion situated in coastal regions, related to the coexistence between the forest remnants and anthropized areas, situated on the same property as consequence of the current legal provisions in the country across Guidelines for the Application of Private Damping Bands – PDBs in Restinga, destined to developments with great environmental impact, licensed through Preliminary Environmental Report or Environmental Impact Study and Environmental Impact Report. The objective was to define interdisciplinary techniques to locate, size and monitor the forest remnant preserved on the property, and also measure the impacts that occur during and after vegetation suppression in the implementation and operation of licensed activity. This work concludes for the viability of the PDBs, after analysis and discussion of the results, legislation, norms, notes and technical opinions related to the Remaining Green Areas on Property, Permanent Preservation and Conservation Units. This last subject focuses on the management and sizing of the Damping Zones, Biomonitoring techniques and Strategic Planning concepts, Landscape Ecology, Dual Territoriality, Socio-Ecological Systems, Adaptive Management and Ecosystem Services.